Analisis Pengaruh Harga Beras, Cadangan Devisa, Dan Rata-Rata Konsumsi Beras per Kapita Seminggu Terhadap Impor Beras Di Indonesia Tahun 2008- 2017 - Niken Puspitasari; Lucia Rita Indrawati; Sudati Nur Sarfiah (DINAMIC : Directory Journal of Economic, 2019)
Food is a basic human need for life, so food commodities are the top priority in the consumptionof the Indonesian population Rice is the most excessively  consumed food commodity by theIndonesian population. Maintaining the availability of domestic rice by importing rice as a government effort to maintain price stability, domestic rice supply and rice reserves when natural disasters  occur. When  itis still  consumed  by  the  majority  of the Indonesian population,  the availability  is  very  crucial.  The  constraints  faced  by  the  supply  of  rice  commodities  are production problems and price stability. Domestic production still does not fulfill consumption so rice imports must be made. The purpose of this research is to determine the effect of rice imports as a government policy to realize food security and food self-sufficiency in Indonesia by knowing the simultaneous and partial influence of rice prices, foreign exchange reserves and rice consumption on rice imports in Indonesia in 2008-2017, and to analyze the most dominant variable  affecting  rice  imports  in  Indonesia  for  the  period  2008-2017.  The  data  analysis technique used is regression analysis and classic assumption test. The results how simultaneously the variable price of rice, foreign exchange reserves and rice consumption have a significant effect on rice imports in Indonesia in 2008-2017. Partially the rice price variable and rice consumption have no effect on rice imports in Indonesia in 2008-2017. The variable of foreign exchange reserves has a positive and significant effect on rice imports in Indonesia in 2008-2017.  Keywords:  Rice  Prices,  Foreign  Exchange  Reserves,  Rice  Consumption,  rice  imports.